How to Predict Business Income on Business Capital, Green Business Practice Adoption, Leadership for Small and Medium-Size Industries in East Java - Jeni Susyanti; Ahmad Dahlan; Achmad Ghazi Bagaskara (Universitas Negeri Semarang, 2023)
This study aims to determine the prediction of business income for Small and Medium Industries through business capital, green business practice adoption, and leadership. The sampling technique using purposive sampling obtained a data sample of 40 respondents from the population. Methods of data collection using a questionnaire method. The data analysis technique used in this study is multiple linear regression. The results of this study indicate that business capital variable can positively and significantly predict business income, green business practice adoption can predict positively and significantly to business income. leadership can positively and significantly predict business income. although as is known, working from home was carried out during the covid 19 pandemic. We found that the TPB theory has good explanatory power decision making to adopt green business in running SMIs